Intervention strategies for emerging viruses: use of antivirals - Debing, Yannick (Curr Opin Virol, 2013)
Today, small molecule antiviral drugs are available for the treatment of infections with herpesviruses, HIV, HBV and HCV as well as with influenza viruses. Ribavirin, a broad-spectrum (but aspecific) antiviral, has been approved for the treatment of infections with respiratory syncytial virus, HCV and Lassa virus. Yet, for many other viruses that cause life-threatening infections [most of which are considered emerging and/or neglected] there are no drugs available. Ideally, potent and broad-spectrum (i.e., pan-genus or pan-family virus activity) antiviral drugs should be developed whereby one drug could be used for the treatment of a number of such viral infections. We here review recent evolutions in the search for inhibitors of emerging and neglected RNA viruses.